Role of FaSOC1 and FaCO in the seasonal control of reproductive and vegetative development in the perennial crop Fragaria × ananassa - Muñoz-Avila, Julio C.; Prieto, Concepción; Sánchez-Sevilla, José F.; Amaya, Iraida; Castillejo, Cristina (Frontiers in Plant Science, 2022)
The diploid woodland strawberry (F. vesca) represents an important model for the genus Fragaria. Significant advances in the understanding of the molecular mechanisms regulating seasonal alternance of flower induction and vegetative reproduction has been made in this species. However, this research area has received little attention on the cultivated octoploid strawberry (F. × ananassa) despite its enormous agronomical and economic importance. To advance in the characterization of this intricated molecular network, expression analysis of key flowering time genes was performed both in short and long days and in cultivars with seasonal and perpetual flowering. Analysis of overexpression of FaCO and FaSOC1 in the seasonal flowering ‘Camarosa’ allowed functional validation of a number of responses already observed in F. vesca while uncovered differences related to the regulation by FaFTs and gibberellins (GAs). While FvCO has been shown to promote flowering and inhibit runner development in the perpetual flowering H4 accession of F. vesca, our study showed that FaCO responds to LD photoperiods as in F. vesca but delayed flowering to some extent, possibly by induction of the strong FaTFL1 repressor in crowns. A contrasting effect on runnering was observed in FaCO transgenic plants, some lines showing reduced runner number whereas in others runnering was slightly accelerated. We demonstrate that the role of the MADS-box transcription factor FaSOC1 as a strong repressor of flowering and promoter of vegetative growth is conserved in woodland and cultivated strawberry. Our study further indicates an important role of FaSOC1 in the photoperiodic repression of FLOWERING LOCUS T (FT) genes FaFT2 and FaFT3 while FaTFL1 upregulation was less prominent than that observed in F. vesca. In our experimental conditions, FaSOC1 promotion of vegetative growth do not require induction of GA biosynthesis, despite GA biosynthesis genes showed a marked photoperiodic upregulation in response to long days, supporting GA requirement for the promotion of vegetative growth. Our results also provided insights into additional factors, such as FaTEM, associated with the vegetative developmental phase that deserve further characterization in the future.